Sulfur transformation mechanism during supercritical water gasification of black liquor. (15th April 2023) - Lu, Libo; Wei, Wenwen; Liu, Fan; Ge, Zhiwei; Jin, Hui; Chen, Yunan; Guo, Liejin
Graphical abstract: Highlights: The maximum carbon gasification efficiency of 95.16% was obtained. The COD removal rate was up to 99.98%. The sulfur transformation characteristics and mechanisms were proposed. Gasification performance showed significant effect on sulfur transformation. Sulfur compounds of black liquor in SCWG were mainly converted into H2 S/S 2− . Abstract: Supercritical water gasification (SCWG) was a promising technology to treat black liquor harmlessly and recycle energy efficiently, while the sulfur transformation of black liquor during SCWG process remained unknow. Herein, the effects of different parameters on gasification and sulfur transformation was determined in a batch reactor. The results showed that reaction temperature played the most important role. H2 was the most important gaseous product with the maximum yields of 19.01 mol·kg −1, simultaneously achieving the highest carbon gasification efficiency (95.16 %), COD removal rate (99.98 %) and the pH of 8.5 at 700 °C, 30 min and 25 MPa. After SCWG treatment, most of sulfur existed in the form of sulfide (H2 S/S 2− ), and the maximum proportion of which was up to 90.51 % at 700 °C, 30 min and 25 MPa. With the increase in temperature, the organic sulfur (thiol/thioether, sulfone and thiophene) and inorganic sulfur (sulfate and thiosulfate) were transformed into sulfide (H2 S/S 2− ). Finally, the sulfur transformation mechanisms of black liquor in SCWG were proposed. This work provided a basis for resource utilization of black liquor and a promising method for sodium sulfide production.